Influence Of The Academic Library Of University Of Buea On Faculty Of Education Postgraduate Students’ Academic Assistance - Mbah Relean-Jeans (Research Parks Publishers, 2021)
Owing to the unavoidable significance of academic library in an institution of higher learning, an investigation whose primordial objective is to reveal an existing relationship between the facilities and services of this information hub and students’ academic assistance should be treated with absolute importance. This research was necessitated by the doubtful nature of somewhat subtle academic assistance which postgraduate students in the Faculty of Education presumably obtained from University of Buea academic library. Consequently, the research was conducted at the Faculty of Education in University of Buea using descriptive research design on a population that comprised 150 postgraduate students. Proportionate stratified and simple random sampling techniques were adopted in the selection and use of a sample size of 60 Master and PhD students which represented 40% of the population. Consequently, 60 copies of questionnaire which was the lone instrument for data collection, and titled Influence of Academic Library on Faculty of Education Postgraduate Students’ Academic Assistance (IAL-FEPSAA) were administered on respondents. For easy understanding of research data computation, non-parametric statistics mainly percentage was used in analyzing respondents’ points of view. Some major findings of the research which stipulated that American Corner and e-books had a positive significant influence on Faculty of Education postgraduate students’ academic assistance, were directed to students and the library authorities. Owing to the educational and academic nature of events organized at American Corner of University of Buea library, it was recommended that Faculty of Education postgraduate students should be encouraged to attend educative talks, seminars, conferences, workshops and symposiums delivered at this venue.